African Asylum at a Crossroads Activism, Expert Testimony, and Refugee Rights - Berger, Iris; Hepner, Tricia; Lawrence, Benjamin; Tague, Joanna; Terretta, Meredith (Ohio University Press, 2015)
This book examines the emerging trend of requests for expert opinions in asylum hearings or refugee status determinations. It is the first to explore the role of court-based expertise in relation to African asylum cases and the first to establish a rigorous analytical framework for interpreting the effects of this new reliance on expert testimony. Courts in Western countries and beyond have begun demanding expert reports tailored to the experience of the individual claimant. As courts increasingly draw upon such testimony in their deliberations, expertise in matters of asylum and refugee status is emerging as an academic area with its own standards, protocols, and guidelines.